Vitamin D effects on Chlamydia trachomatis infection: a case-control and experimental study - Liu, Sijia; Zhao, Tianwei; Liu, Quanzhong (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction: Vitamin D deficiency is the most common nutritional deficiency worldwide. Chronic vitamin D deficiency causes immune system dysfunction, which increases susceptibility to pathogens such as bacteria, especially intracellular parasites, and viruses. Chlamydia trachomatis (C. t) is an obligate intracellular parasitic bacterium that causes a variety of sequelae. We speculated that vitamin D might be associated with C. t infection. This study aimed to address this gap in knowledge by investigating the relationship between vitamin D and C. t infection using both in vitro and in vivo models. Methods and Results: The addition of calcitriol to McCoy cell culture in vitro delayed and reduced the quantity and volume of inclusions compared to the control group. Macrophages of peritoneally lavaged mice co-cultured with McCoy decreased the infection rate and delayed the appearance of inclusions. In mice models of vitamin D deficiency, mice in the VD group exhibited more severe genital tract inflammation and a longer duration of infection after inoculation with C. t in the genital tract. Supplementing these mice with vitamin D during treatment enhanced the therapeutic effect of antibiotics. We also conducted a case-control study involving 174 C. t-positive patients (95 males and 79 females) and 380 healthy volunteers (211 males and 169 females) aged 20-49 from January 2016 to March 15, 2017. Serum 25-(OH)D concentration was measured by assessing morning fasting blood samples of healthy volunteers and C. t-positive patients 1 day before antibiotic treatment and the next day after one course of treatment. The patients were followed up for 1 month and evaluated for recovery. The results showed that vitamin D deficiency was a risk factor for C. t infection and treatment failure. Conclusion: In summary, findings from experimental and clinical studies indicate a close association between vitamin D levels and C. t infection and treatment outcomes. Given the affordability and safety of vitamin D, both healthy individuals and patients should focus on vitamin D intake. Vitamin D supplementation could enhance treatment success and should be used as an adjunctive therapy alongside antibiotic therapy for C. t infections, pending confirmation in larger, prospective, randomized controlled trials.